Effect of Coriander Seeds as Diet Ingredient on Blood Parameters of Broiler Chicks Raised under High Ambient Temperature - Al-Jaff, Farah K. (International Journal of Poultry Science, 2011)
This Study was conducted to investigate the potential effect of coriander seeds on physiological traits. One hundred and eighty day-old Arbor Acer broiler chick were randomly assigned to four dietary treatments with three replicate pens (15 birds/pen). Birds were fed experimental diets containing 0% (T1), 1% (T2), 2% (T3) and 3% (T4) coriander seed. Feed and water were provided ad libitum during the experiment. Performance and physiological parameters were monitored at the end of the study (6 weeks of age) which includes live body weight, feed conversion ratio (g. Feed gain/g. Gain) total protein, albumin, globulin, A/G ratio, GTP, GOT, Alkaline phosphatase, glucose, cholesterol, LDL, HDL, Triglycerides, phospholipids, uric acid, creatinine and antibody titer (ND). Results showed that final body weight was (p<0.01) higher in 2% coriander seed (T3) than all other groups and feed conversion ratio was significantly (p<0.05) better for birds that were fed 2% (T3) and (T4) coriander seed than all other groups. Serum protein and albumin were (p<0.05) higher in 2% (T3), While serum globulin (p<0.05) lower in 2% coriander seed (T3) when compared with other groups. GOT and GPT were (p<0.05) lower for 2% (T3) and 3% (T4) coriander seed, while alkaline phosphatase was (p<0.05) lower in 2% (T3) group. Serum glucose (p<0.05) lower in 2% (T3) coriander seed than all other group, Serum cholesterol was (p<0.05) lower in 2% (T3) and 3% (T4) compared with other groups. LDL was (p<0.05) lower in (T3) group, while HDL was (p<0.05) lower in T3 and T4 groups when compared with the control. Serum triglycerides and antibody titers were (p<0.05) higher in 2% and 3% coriander seed when compared with other groups. It could be concluded from this study that the inclusion of coriander seeds at levels of 2% have a positive effect on blood pictures, broiler performance and immune system during heat stress (high ambient temperature).